MEDIA VIABILITY AND NATIONAL RESILIENCE: ENTREPRENEURIAL COMMUNICATION MODELS FOR CONFRONTING FOOD AND SECURITY CRISES IN NIGERIAeria (AUN INTERNATIONAL CONFERENCE, 2025)
Persistent food insecurity and multidimensional security crises in Nigeria reveal the fragility of governance and information systems of the country. While the media are central to the national response to crises, little attention has been paid to the viability and sustainability of media institutions themselves as infrastructures of resilience. This study examines the relationship between economic sustainability, technological innovation, and civic trust and how this relates to the media's ability to communicate effectively during food and security crises.  Anchored in Media Viability Theory, Resilience Communication Framework and Innovation Diffusion Theory, the research uses qualitative research design which is interpretive, document analysis and in depth interviews with journalists, policy makers and development partners.  Findings show that in the context of the information era, low economic resilience, technological divide and crisis of public trust have the combined effect of weakening crisis communication and public participation. The paper proposes a Media Viability - Resilience Framework (MVRF) that combines economic sustainability, technological adaptability, and civic trust as interdependent capacities leading to institutional media resilience that leads to national resilience. By linking communication studies, development policy and security research, this research provides a multi-disciplinary model in repositioning Nigerian media as an institutional actor in resilience governance, as well as a strategic driver of informed and participatory responses to the country's food and security problems